2019
DOI: 10.1177/2055217319848463
|View full text |Cite
|
Sign up to set email alerts
|

Distinct serum and cerebrospinal fluid cytokine and chemokine profiles in autoantibody-associated demyelinating diseases

Abstract: Background Demyelinating diseases of the central nervous system associated with autoantibodies against aquaporin-4 and myelin-oligodendrocyte-glycoprotein are mediated by different immunopathological mechanisms compared to multiple sclerosis. Objective The purpose of this study was to evaluate serum and cerebrospinal fluid cytokine/chemokine profiles in patients with autoantibodies against aquaporin-4 or autoantibodies against myelin-oligodendrocyte-glycoprotein-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…The composition of CSF is close to that of serum, albeit with slightly different electrolyte levels and considerably lower protein concentration 27 . Recent studies have accurately determined the levels of proteins particularly cytokines including chemokine in both serum and CSF using an ELISA-like method, indicating that such tests can be used with both sample types 28 . Although diagnostic laboratory tests in CSF were only recently standardized, they are now sufficiently accurate to contribute to the diagnosis of conditions that compromise the blood-brain barrier, including MS and Alzheimer’s disease 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The composition of CSF is close to that of serum, albeit with slightly different electrolyte levels and considerably lower protein concentration 27 . Recent studies have accurately determined the levels of proteins particularly cytokines including chemokine in both serum and CSF using an ELISA-like method, indicating that such tests can be used with both sample types 28 . Although diagnostic laboratory tests in CSF were only recently standardized, they are now sufficiently accurate to contribute to the diagnosis of conditions that compromise the blood-brain barrier, including MS and Alzheimer’s disease 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…6 So far, only case reports were available on the neuropathology associated with MOG-IgG in patients with inflammatory demyelinating diseases (reviewed The importance of T-cell mediated inflammation was recently confirmed in two studies analysing serum and CSF cytokine and chemokine profiles in MOG-IgG positive patients. 143,144 Both studies demonstrated that the CSF cytokine and chemokine profile associated with MOG-IgG is similar to AQP4-IgG positive NMOSD and distinct from MS. The inflammatory profile is characterized by coordinated upregulation of T helper 17 and other cytokines, particularly of interleukin-6.…”
Section: Pathology and Pathophysiology Of Mog-igg Associated Diseasesmentioning
confidence: 99%
“…Numerous studies indicate that sera from MS patients have elevated levels of IL-6. However, studies suggest no quantitative change compared to control groups or only minor signs [9][10][11]. During relapses and in association with existing neurological impairment, the serum of MS patients with relapsing-remitting disease has elevated IL-6 [12,13].…”
Section: Introductionmentioning
confidence: 99%